The Impact of Counseling on the Anxiety Level of the Surrounding Community Due to Positive Indication of Residents of Covid-19 - Jujuk Proboningsih; Endah Suprihatin; Anita Joeliantina; Aida Novita Sari; Fathimath Shifaza (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
This pandemic period has multiple impacts on all aspects of life. Both economic, social, religious, and psychological. The psychological side is the great fear in the community as the virus spreads very quickly from the sick to the healthy. Changes in interpersonal relationships and in the economy are often followed by changes in politics, including the life of the nation and the state. Various everyday problems also need to be observed and solved with new approaches. The aim of this research is to examine the impact of counseling on the anxiety level of the surrounding community due to residents found to have positive COVID-19 infection. So that people can understand Covid-19 properly and don't experience anxiety even though there are local residents who are confirmed positive for Covid-19. This study was a quasi-experimental study with a pre-post test control group design. The purpose of this study was to analyze the effectiveness of counseling in reducing anxiety levels in the surrounding community due to residents indicated as positive for Covid-19. Test results showed a significant difference in the treatment group before (pre-test) and after (post-test) counseling (p-value 0.000). The test results between the treatment group and the control group also showed a significant difference in the post-test (p-value of 0.000). Anxiety or stress during this pandemic leads to an increase in concern for one's own health and that of the family. The situation is exacerbated by the fact that information arriving in bewildering abundance will increase public anxiety. There is a need for participation and collaboration between health care facilities and health care workers and health cadres to provide accurate information so that people are properly informed and can reduce their fears so that they are able to take appropriate action. There is a significant effect of counseling to reduce the anxiety level of the surrounding community due to residents who tested positive for Covid-19.